An Assessment of Two Types of Industrially Produced Municipal Green Waste Compost by Quality Control Indices - Daniela V. Borisova; Gergana S. Kostadinova; Georgi S. Petkov; Diyana M. Dermendzhieva; Georgi G. Beev (Applied Sciences, 2022)
Municipal green waste (MGW) has significantly increased with the development of urban green areas, and its utilization by composting is a good alternative to solve the problem. This paper presents the results from the quality assessment of two industrial composts (from the composting facility of a regional nonhazardous waste landfill) based on their physicochemical properties, hygienic safety (microbiological parameters), fertilizing potential (by fertilizing index, FI) and heavy metal polluting potential (by clean index, CI). Compost 1 (C1) was made from MGW (100%) and Compost 2 (C2) was made from MGW (75%) and discarded green peppers (25%). The evaluation of physicochemical parameters was conducted according to Bulgarian Standards (BDS) methods and microbiological analysis using selective, chromogenic detection systems. It was found that the EC, P, K, Mg, Cu, Cr and Ni were lower for C1 (p < 0.05–0.001). On the other hand, Pb concentration was higher compared to C2 (p < 0.001); the concentrations of Cd, Hg and the E. coli were very low for both composts; presence of Salmonella was not detected. The estimated quality indexes (FI and CI) classified C1 as Class B compost (very-good-quality compost with medium fertilizing potential) and C2 as Class A compost (best-quality compost with high soil fertility potential and low heavy metal content). The C1 and C2 composts meet the requirements of EU and Bulgarian legislation and can be used as soil fertilizers.